4(d-2)=3(d+6)

Simple and best practice solution for 4(d-2)=3(d+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(d-2)=3(d+6) equation:


Simplifying
4(d + -2) = 3(d + 6)

Reorder the terms:
4(-2 + d) = 3(d + 6)
(-2 * 4 + d * 4) = 3(d + 6)
(-8 + 4d) = 3(d + 6)

Reorder the terms:
-8 + 4d = 3(6 + d)
-8 + 4d = (6 * 3 + d * 3)
-8 + 4d = (18 + 3d)

Solving
-8 + 4d = 18 + 3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3d' to each side of the equation.
-8 + 4d + -3d = 18 + 3d + -3d

Combine like terms: 4d + -3d = 1d
-8 + 1d = 18 + 3d + -3d

Combine like terms: 3d + -3d = 0
-8 + 1d = 18 + 0
-8 + 1d = 18

Add '8' to each side of the equation.
-8 + 8 + 1d = 18 + 8

Combine like terms: -8 + 8 = 0
0 + 1d = 18 + 8
1d = 18 + 8

Combine like terms: 18 + 8 = 26
1d = 26

Divide each side by '1'.
d = 26

Simplifying
d = 26

See similar equations:

| y=7/4(4)+3 | | y=7/4(2)+3 | | y=7/4(0)+3 | | 86x+2x=256-9x | | y=7/2(1)+6 | | y=7/2(2)+6 | | 3m^2-5m+8=(m-1)(3m+2) | | y=7/2(3)+6 | | 3-c=12-2c | | y=7/2(6)+6 | | 450000-22000x=155000+12000 | | y=7/2(0)+6 | | 3m^2-5m+8=0 | | 15x+30=40x-180 | | 3a-6=a | | 10x+20=50x-225 | | 14-(6x)=32 | | 5z^2-25z-az-5a=0 | | 10z/7x | | 0.5x-0.2(80+x)=0.1(80) | | 10x/7x | | -0.7(20)+0.8x=0.2(20+x) | | 1b=1p+1s | | 1p+1s=1b | | 4/x-2=-6/x+2+6/(x-2)(x+2) | | 5x/x*x-4=10/x*x-4-2/x+2 | | x(6x-6)=(6x+9)(x-1) | | 8000000+209.00x=599.00x | | v=3.14(8)2(10) | | 27-3u^2/u^2+3u-18 | | -6x-10(x-2)=-16 | | 275000=45000x |

Equations solver categories